Research into biotechnological processes of plant Snutrition stimulation by the products of phosphogypsum disposal in gas cleaning systems - Plyatsuk, Leonid; Chernysh, Yelizaveta; Ablieieva, Iryna; Burla, Oksana; Hurets, Larysa (Eastern-European Journal of Enterprise Technologies, 2018)
The rational qualitative and quantitative composition of granules of phosphogypsum that is used as the load for the systems of biochemical cleaning of gas emissions was established. The study of the zones of biotransformation of phosphogypsum component with the use of raster microscopy was performed. The biofilm, formed by sulfur oxidizing bacteria on the surface of granules, and elementary sulfur that is metabolite, deposited during oxidation of hydrogen sulfide, were explored. Physical and chemical properties of biosulfur, produced as a result of biochemical gas cleaning of sulfur-containing gas flows in biofilters with the load from phosphogypsum, were determined. We analyzed the models of metabolic pathways of sulfoxydizing bacteria, providing oxidation of sulfur-containing compounds into the forms that are easily accessible for plants using electronic databases, such as KEGG database, MetaCyc and EzTaxon databases. The biochemical mechanisms of transformation of biosulfur when using it in the process of S-nutrition of plants were determined, which will make it possible to dispose of it in agroecosystems. The combined scheme of the ways of bacterial oxidation of sulfide to sulfate was substantiated. The species structure of ecological and trophic groups of microorganisms, involved in oxidation of sulfur, among which hemolithotrophic bacteria of the genus Thiobacillus are dominant, was assessed. The general technological scheme of the phosphogypsum disposal with the production of biosulfur in the systems of biochemical gas cleaning was developed. Environmental effects from implementation of the proposed technological system were obtained: impurities (hydrogen sulfide, carbon dioxide) were removed from gas emissions; the waste of chemical industry – dump phosphogypsum was disposed of; biosulfur as a product, used to improve S-nutrition in agroecosystems, was produced